2013
DOI: 10.1371/journal.pone.0065351
|View full text |Cite
|
Sign up to set email alerts
|

Active Video Games and Health Indicators in Children and Youth: A Systematic Review

Abstract: BackgroundActive video games (AVGs) have gained interest as a way to increase physical activity in children and youth. The effect of AVGs on acute energy expenditure (EE) has previously been reported; however, the influence of AVGs on other health-related lifestyle indicators remains unclear.ObjectiveThis systematic review aimed to explain the relationship between AVGs and nine health and behavioural indicators in the pediatric population (aged 0–17 years).Data sourcesOnline databases (MEDLINE, EMBASE, psycINF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
181
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(214 citation statements)
references
References 64 publications
10
181
1
8
Order By: Relevance
“…Another limitation of this study was the small sample size, which hindered the statistical power of the analysis. Reviews on gaming health literature by LeBlanc et al [25] and Kharrazi et al [6] have identified low sample size as a consistent issue that arises in this field of research. Comparable studies by Ballard et al [7] and Weaver et al [9] also had limited sample size with 116 and 562 participants respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study was the small sample size, which hindered the statistical power of the analysis. Reviews on gaming health literature by LeBlanc et al [25] and Kharrazi et al [6] have identified low sample size as a consistent issue that arises in this field of research. Comparable studies by Ballard et al [7] and Weaver et al [9] also had limited sample size with 116 and 562 participants respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous empirical studies and systematic reviews have primarily relied on P values. 8,9,16 Effect sizes, however, are more appropriate for intervention evaluation. 17,18 Although the flaws of null-hypothesis significance testing have been discussed …”
Section: Discussionmentioning
confidence: 99%
“…The conclusion of Larsen et al 9 is that more research is necessary to study the effects of active videogames for the elderly. Another recent systematic review 8 concluded that active videogames result in acute energy expenditure, but that it is not clear if active videogames result in longer-term health benefits. The preliminary estimates provided by the present meta-analytic procedures suggest that active videogames do indeed lead to improvements in children's BMI and in functional balance in the elderly.…”
Section: Effectiveness Of Active Videogamesmentioning
confidence: 99%
See 2 more Smart Citations